Singapore's Water Strategy: Diversified, Robust, and Sustainable. Issue 6 (2nd June 2020) - Seah, Harry
Key Takeaways: Driven mostly by industrial development, demand for water in the island city‐state of Singapore is expected to almost double by 2060. The use of reclaimed water (known as NEWater) is the most sustainable and cost‐effective way to boost Singapore's water supply for the long term. Singapore's national water agency is encouraging companies in water‐intensive industries to implement innovative solutions to improve water sustainability.